Domestic Violence Among Women Attending to Psychiatric Outpatient Clinic - YORGUNER, NEŞE; AKVARDAR, YILDIZ (AVES, 2018)
Objective: Domestic violence (DV) is defined as all kinds of abusive behaviors between spouses or relatives living in the same house. Domestic violence is most commonly directed towards women and children. This study aims to review the extent of domestic violence among women consulting to psychiatric outpatient clinic, and to identify its relation with sociodemographic risk factors and psychological symptoms. Method: Self-reported Domestic Violence Questionnaire and Symptom Checklist-90-R (SCL-90-R) information was collected from women who admitted to psychiatric outpatient clinic at Marmara University Research and Educational Hospital, and accepted to participate in the study. Results: 300 women participated in the study. Mean age of participants was 36.24 +/- 10.88, 75.7% of them were married, and mostly live within nuclear families. 70.1% of the participants reported verbal violence, and 49.0% reported physical violence. 65.3% of those who have experienced verbal violence have also experienced physical violence. 26.1% of them reported as not having experienced domestic violence before. The nature and extent of domestic violence, women's attitudes towards it, and its relation with experience of domestic violence during childhood have been explored. Participants' educational levels, current age and age of marriage, style of marriage, educational level and age of spouse were not found to be associated with experiencing of domestic violence. Both verbal and physical domestic violence were significantly associated with the economic status of women (p<0.05). The mean SCL-90-R score was 1.40 +/- 0.68 with the highest mean subgroup score under depressive symptoms category (1.80 +/- 0.79). Mean SCL-90-R score showed significant association with the experience of domestic violence (p <= 0.001). Conclusion: Most of the women participated in the study have experienced domestic violence. Both verbal and physical violence increased with lower economic status. Psychiatric symptoms increased with the experience of domestic violence. Considering its high prevalence and detrimental psychological effects, domestic violence should be inquired by clinicians as part of the psychiatric interview.
Keywords: Domestic violence; violence; women; psychiatric symptoms; INTIMATE PARTNER VIOLENCE; MARRIED-WOMEN; PREVALENCE; HEALTH; DEPRESSION